2021
DOI: 10.14254/2071-8330.2021/14-2/2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Industry 4.0 on the selected macroeconomic indicators in Slovak Republic, Germany, the USA and Japan

Abstract: Rapid development of communication and information technologies with their orientation on big data have significantly changed the character and the needs of national economies. The onset of the 4th Industrial Revolution significantly affects the structural changes of individual economies (companies) as well as their requirements for workforce. The Industry 4.0 concept was created in Germany, and now is being implemented in various countries under different names. In our study, we focus on the development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Another study, examining different selected economic indicators over the same time, points to the development of GDP in connection with the share of university-educated workers. It is concluded that Industry 4.0 initiative in Slovakia raises greater need to increase educational potential of employees, even with the expected future increase in staff qualification requirements, unlike developed countries like Germany or Japan, where the share of university-educated workers have been rising for several years now (Habánik et al, 2021).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Another study, examining different selected economic indicators over the same time, points to the development of GDP in connection with the share of university-educated workers. It is concluded that Industry 4.0 initiative in Slovakia raises greater need to increase educational potential of employees, even with the expected future increase in staff qualification requirements, unlike developed countries like Germany or Japan, where the share of university-educated workers have been rising for several years now (Habánik et al, 2021).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The study marks the transport sector as crucial in the current economic situation. Honkova adds [88] that the transport sector plays a significant role in ensuring competitiveness and sustainable economic growth in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In higher educational institutions of the US, Slovakia, Germany, and Japan, the University 4.0 model is in great demand due to its notable influence on learning effectiveness. Another reason for it to become so popular lies in that it is based on an interdisciplinary approach and relies upon the development of professional competencies using the latest interactive technologies, which increases students' learning motivation [51]. On the other hand, University 4.0 model still has prospects for growth.…”
Section: Discussionmentioning
confidence: 99%